Scientific Applications of Unmanned Vehicles in Svalbard (UAV Svalbard) - Hann, Richard; Altstädter, Barbara; Betlem, Peter; Deja, Kajetan; Dragańska-Deja, Katarzyna; Ewertowski, Marek; Hartvich, Filip; Jonassen, Marius; Lampert, Astrid; Laska, Michał; Sobota, Ireneusz; Storvold, Rune; et al. (Zenodo, 2021)
This is chapter 3 of the State of Environmental Science in Svalbard (SESS) report 2020 (https://sios-svalbard.org/SESS_Issue3). The polar regions are among the most sensitive areas of the Earth and changes in the Arctic have global consequences. Therefore, more and better Arctic research is needed, and unmanned vehicles are an important tool in this research. This report provides a review of research conducted with unmanned vehicles in Svalbard. That includes vehicles that travel in air, on water and underwater. The main focus is on unmanned aerial vehicles (UAVs). UAVs are well-suited for Arctic research for several reasons. The Arctic regions lack high vegetation and big settlements, making them ideal for aerial observations. UAVs can access glaciers, mountains, and other difficult areas. They are cheaper and have a lower environmental impact than manned flights. Svalbard has an international research infrastructure and frequent flight connections, making it a hotspot for Arctic research. However, there are several challenges to the use of unmanned vehicles in the Arctic. These include magnetic interference, low temperatures, harsh weather conditions, and wildlife. Most optical sensors cannot be used during the dark season between October and February. This review shows that the researchers using unmanned vehicles in Svalbard can be divided into two groups: basic and advanced users. The majority of researchers today are basic users. They use off-the-shelf UAVs to enhance their fieldwork. The most common application is mapping. A minority of the researchers are advanced users. This group includes users of unmanned marine vehicles and fixed-wing UAVs.